Fundamental financial accounting concepts - Edmonds, Thomas P.; Edmonds, Christopher T.; Edmond, Mark A.; Edmonds, Jennifer E.; Olds, Philip R. (McGraw-Hill, 2022)
"Technology has changed accounting practice. Gone are the days where accountants used pens, paper, and calculators to maintain records and prepare statements. Indeed, most companies use computer software that simplifies data entry, recordkeeping, and statement preparation. Today's accountants spend less time preparing financial information and more time consulting and advising clients. To remain relevant, accounting education must move beyond the traditional preparer approach. The first step in learning how to advise clients is to understand how business professionals incorporate accounting in the decision-making process. Business professionals tend to think about bottom-line consequences. If I do this or that, how will it affect my company's net income, total assets, cash flow, and so on. To promote bottomline thinking, we take the student one step beyond the recording process. Specifically, we employ a financial statements model to show them how the journal entries affect financial statements. The model arranges the balance sheet, income statement, and statement of cash flows horizontally across a single line of text"--Provided by publisher.